2018
DOI: 10.1093/labmed/lmx080
|View full text |Cite|
|
Sign up to set email alerts
|

Cervical Cancer Markers: Epigenetics and microRNAs

Abstract: Gynecologic malignant neoplasms are a severe health problem among female patients, of which cervical cancer (CC), in particular, is a common disease leading to high mortality rates. Despite extensive attempts by researchers to solve the molecular mystery of CC, the mechanisms of its pathogenesis remain unclear. Tumor markers used in the clinical laboratory, such as squamous cell carcinoma (SCC), cancer antigen (CA)-125, and CA19-9, provide some help in diagnosing patients with CC. However, finding new molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 133 publications
2
73
0
2
Order By: Relevance
“…MiRNAs may function either as oncomiRs or tumor suppressor miRNAs depending on their target genes (Xia et al, 2016). In particular, a wide range of miRNAs are dysregulated in cervical cancer and are involved in the modulation of various pathological and physiological phenomena, including cell proliferation, the cell cycle, apoptosis, metastasis, angiogenesis, and chemoresistance (Feng et al, 2017;Li et al, 2017;Laengsri et al, 2018). Therefore, miRNAs may be promising therapeutic targets for the management of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs may function either as oncomiRs or tumor suppressor miRNAs depending on their target genes (Xia et al, 2016). In particular, a wide range of miRNAs are dysregulated in cervical cancer and are involved in the modulation of various pathological and physiological phenomena, including cell proliferation, the cell cycle, apoptosis, metastasis, angiogenesis, and chemoresistance (Feng et al, 2017;Li et al, 2017;Laengsri et al, 2018). Therefore, miRNAs may be promising therapeutic targets for the management of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the dysregulation of miRNAs has been reported to contribute to a number of processes associated with cancer pathophysiology, including cell proliferation, cell cycle, apoptosis, epithelial-mesenchymal transition, metastasis, angiogenesis and resistance to chemoand radiotherapy (32)(33)(34). Therefore, a thorough understanding of the mechanism underlying cervical cancer carcinogenesis and progression is crucial for early diagnosis and improving patient outcome (14). In particular, further exploration on the specific roles of dysregulated miRNAs in cervical cancer and their associated mechanism may provide an avenue for the development of effective therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…To date, >2,500 miRNAs have been identified in the human genome (12), with ~60% of protein-coding genes reported to be targeted by miRNAs (13). Dysregulation of miRNA function has been documented in nearly all types of human malignant tumors such as cervical cancer (14)(15)(16). miRNAs may be involved in the modulation of cervical carcinogenesis and progression by acting as either oncogenes or tumor suppressors (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs of 18‐22 nucleotides (nt) in length that are able to bind to the 3′‐UTR of specific mRNA targets to regulate their translation at the post‐transcriptional level . Several previous studies have demonstrated that some miRNAs are dysregulated in many cancers, especially in CC . For example, miR‐374b inhibited cell proliferation and induces apoptosis through the p38/ERK signaling pathway by binding to JAM‐2 in cervical cancer .…”
Section: Introductionmentioning
confidence: 99%